Accountability Mechanism in Village Owned Financial Institutions: A Case Study on Communal-Based Financial Institutions in West Sumatra - Cicalarici, Cicalarici; Fauzi, Nurul; Rosita, Irda (Economics, Business, Accounting & Society Review, 2023)
This study aims to determine how the accountability mechanism practised by Village Owned Financial Institutions (called LPN) of Limau Manis Padang is viewed from the perspective of a disclosure statement and report, performance assessment and evaluation, participation, self-regulation, and social auditing. LPN is a communal-based microfinance institution that once experienced its glory in West Sumatra during the 1970s and 1990s. This research uses an interpretive qualitative paradigm. The data used in this study are primary. Data was collected by in-depth interviews (in-depth interviews), observations, and document reviews. Informants are selected using snowball sampling patterns. This research found that LPN Accountability has not been implemented perfectly, especially in reporting and disclosure accountability. The public cannot easily access information on the LPN report. In addition, LPN has not practised aspects of social audits that provide opportunities for the public to conduct voluntary audits and assessments of LPN's internal processes.